Electroactive materials for metal-ion batteries
By depositing silicon electroactive materials in the porous carbon framework to form composite particles, the mechanical stress problems caused by the volume changes of silicon anode material in lithium-ion batteries are solved, and higher electrochemical capacity and more stable cycling performance are achieved.
Patent Information
- Application Number
- CN201980079208.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-09
- Filing Date
- 2019-11-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2039-11-08
AI Technical Summary
In the existing lithium-ion batteries, the use of silicon as an anode material has large mechanical stress due to volume changes, resulting in serious loss of electrochemical capacity, and it is difficult to maintain the stability of the charging-discharge cycle.
A porous carbon skeleton with a specific pore structure and pore size distribution is used as the carrier of the electroactive material, and composite particles are formed by depositing silicon electroactive material in the micropores and mesopores of the porous carbon skeleton to improve the mechanical strength and electrochemical capacity of the material.
By optimizing the pore structure of the porous carbon skeleton, the mechanical strength and electrochemical properties of the composite particles are improved, the capacity loss in the charging-discharge cycle is reduced, and the service life of the battery is extended.
Smart Images

Figure CN113169307B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates generally to electroactive materials suitable for use in electrodes of rechargeable metal ion batteries, and more particularly to particulate materials having high mechanical strength and high electrochemical capacity suitable for use as anode active materials in rechargeable metal ion batteries. Background Art
[0002] Rechargeable metal ion batteries are widely used in portable electronic devices, such as mobile phones and laptops, and are increasingly used in electric vehicles or hybrid vehicles. Rechargeable metal ion batteries generally include an anode layer, a cathode layer, an electrolyte for transporting metal ions between the anode layer and the cathode layer, and an electrically insulating porous separator disposed between the anode and the cathode. The cathode generally includes a metal current collector having a metal oxide composite material layer containing metal particles, and the anode generally includes a metal current collector having an electroactive material layer, which is defined herein as a material capable of embedding and releasing metal ions during charging and discharging of the battery. To avoid doubt, the terms "cathode" and "anode" are used herein in the following sense: the battery is connected to a load so that the cathode is the positive electrode and the anode is the negative electrode. When the metal ion battery is charged, the metal ions are transported from the cathode layer containing the metal ions to the anode via the electrolyte and are embedded in the anode material. The term "battery" herein refers to both a device containing a single anode and a single cathode and a device containing multiple anodes and / or multiple cathodes.
[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal ion batteries. The use of lithium ion batteries has provided substantial improvements when compared to other battery technologies, but there is still room for further development. To date, commercial lithium ion batteries have been largely limited by the use of graphite as the anode active material. When the graphite anode is charged, lithium is intercalated between the graphite layers to form a lithium ion battery with the empirical formula Li x C6 (where x is greater than 0 and less than or equal to 1). Thus, the maximum theoretical capacity of graphite in lithium-ion batteries is 372 mAh / g, with actual capacities slightly lower (approximately 340 to 360 mAh / g). Other materials such as silicon, tin, and germanium can intercalate lithium at significantly higher capacities than graphite, but have not been widely used commercially due to difficulties in maintaining sufficient capacity over multiple charge / discharge cycles.
[0004] In particular, silicon is considered a promising graphite substitute for making rechargeable metal ion batteries with high weight and volumetric capacity due to its very high lithium capacity (see, for example, Insertion Electrode Materials for rechargeable Lithium Batteries, Winter, M et al., Adv. Mater. 1998, 10, No. 10). At room temperature, the theoretical maximum specific capacity of silicon in lithium ion batteries is about 3,600 mAh / g (based on Li 15 However, the use of silicon as an anode material is complicated by the large volume change during charge and discharge.
[0005] The insertion of lithium into bulk silicon results in a substantial increase in the volume of the silicon material, up to 400% of its original volume when silicon is lithiated to its maximum capacity, and repeated charge-discharge cycles induce significant mechanical stresses in the silicon material, leading to fracture and delamination of the silicon anode material. The volume shrinkage of silicon particles during delithiation may result in loss of electrical contact between the anode material and the current collector. Another difficulty is that the solid electrolyte interface (SEI) layer formed on the silicon surface does not have sufficient mechanical tolerance to accommodate the expansion and contraction of silicon. As a result, the newly exposed silicon surface leads to further electrolyte decomposition and increased SEI layer thickness as well as irreversible lithium consumption. These damage mechanisms together lead to unacceptable electrochemical capacity loss during continuous charge and discharge cycles.
[0006] A variety of approaches have been proposed to overcome the problems associated with the volume changes observed when silicon-containing anodes are charged. The most common approach to addressing the irreversible capacity loss of silicon-containing anodes is to use some form of finely structured silicon as the electroactive material. Fine silicon structures such as silicon films and silicon nanoparticles with cross-sections below about 150 nm have been reported to be more tolerant of volume changes during charge and discharge than silicon particles in the micrometer size range. However, none of them are particularly suitable for commercial-scale applications in their unmodified form; nanosized particles are difficult to prepare and handle, and silicon films do not provide sufficient bulk capacity. For example, nanosized particles tend to form agglomerates, making it difficult to obtain a usable dispersion of particles within the anode material matrix. In addition, the formation of agglomerates of nanosized particles leads to unacceptable capacity losses upon repeated charge-discharge cycles.
[0007] Ohara et al. (Journal of Power Sources 136 (2004) 303-306) have described the evaporation of silicon as a thin film onto a nickel foil current collector and the use of this structure as an anode for a lithium ion battery. Although this method gave good capacity retention, the thin film structure did not give a usable amount of capacity per unit area and any improvement was eliminated as the film thickness increased.
[0008] WO 2007 / 083155 discloses that improved capacity retention can be obtained by using silicon particles having a high aspect ratio (ie the ratio of the largest dimension to the smallest dimension of the particle).
[0009] It is also generally known that electroactive materials such as silicon can be deposited in the pores of porous support materials such as activated carbon materials. These composite materials provide some beneficial charge-discharge properties of nanosized silicon particles while avoiding the difficulty of handling nanoparticles. For example, Guo et al. (Journal of Materials Chemistry A, 2013, pp. 14075-14079) disclose a silicon-carbon composite material in which a porous carbon substrate provides a conductive skeleton and silicon nanoparticles are deposited in a uniformly distributed pore structure of the substrate. SEI formation during the initial charge cycle is limited by the remaining pore volume, so that the remaining silicon is not exposed to the electrolyte in subsequent charge cycles. It is known that the composite material has an improved capacity retention rate over multiple charge cycles, but the initial capacity of the composite material (in mAh / g) is significantly lower than the initial capacity of the silicon nanoparticles.
[0010] JP2003100284 discloses an active material comprising a carbon-based scaffold with small pores branching from some larger pores. The electroactive material (eg silicon) is randomly located on the walls of both the large and small pores, as well as on the outer surface of the carbon-based scaffold.
[0011] Despite the efforts made to date, there is a continuing need to improve the electrochemical storage capacity of lithium-ion batteries. Specifically, composite materials that rely on porous support materials with electroactive materials deposited in the pore structure generally have insufficient structural strength for commercial use. Conventional electrode fabrication processes generally rely on calendering the electrode material onto a current collector to densify the electrode layer and optimize space utilization within the battery design. Highly porous materials are susceptible to fracture during electrode fabrication, resulting in compromised electrochemical performance. Summary of the invention
[0012] The present invention is based on the observation that the mechanical properties of composite particles comprising a porous carbon framework and an electroactive material located within the porous carbon framework can be optimized by using a porous carbon framework with a specific pore structure and at the same time a carefully controlled pore size distribution.
[0013] In a first aspect, the present invention provides a particulate material comprising a plurality of composite particles, wherein the composite particles comprise:
[0014] (a) a porous carbon framework comprising micropores and / or mesopores,
[0015] The total pore volume of the micropores and mesopores measured by gas adsorption is P 1 cm 3 / g, where P 1 The value of is at least 0.6,
[0016] Among them, PD measured by gas adsorption 50 Pore diameter does not exceed 2nm; and
[0017] (b) an electroactive material located in the micropores and / or mesopores of the porous carbon framework;
[0018] wherein the composite particle D 90 The particle size does not exceed 10μm.
[0019] The present invention therefore relates to a particulate material wherein the porous carbon framework has a relatively high total volume of micropores and mesopores, wherein pores having a diameter not exceeding 2 nm account for at least 50% of the total pore volume, and the particle size distribution is heavily biased towards particles having a diameter not exceeding 10 μm. For the avoidance of doubt, references herein to the pore volume of the porous carbon framework (in the absence of any contrary indication) relate to the pore volume of the porous carbon framework alone, i.e., the pore volume of the porous carbon framework measured in the absence of any electroactive material (or any other material) occupying the pores of the porous carbon framework.
[0020] It has been found that the combination of small particle size and highly differentiated pore volume provides an electroactive material with high resistance to mechanical degradation during electrode manufacturing. The highly fine pore structure of the porous carbon framework results in very fine pore walls, and without being bound by theory, it is believed that these very fine pore walls can be elastically deformed to reduce the fracture rate, making the framework very resistant to fracture under compressive stress. Controlled pore size distribution additionally contributes to particle strength, as well as achieving improved close packing of composite particles in the electrode active layer, thereby reducing the need for excessive calendering pressure.
[0021] Another benefit of the particulate material of the present invention is that the highly microporous carbon framework has a high tensile fracture strength and can therefore accommodate expansion of at least a portion of the electroactive material within the pore volume without fracture. Although complete lithiation of the electroactive material may result in some external expansion of the entire composite particle, the amount of external expansion is limited because the expansion is accommodated internally. The highly microporous carbon framework is able to deform without fracture in terms of outward expansion of the material. The high total porosity of the porous carbon framework not only provides a high volumetric loading of the electroactive material, but also ensures that the porous carbon framework is sufficiently resilient to withstand repeated volume changes during multiple charge-discharge cycles.
[0022] Highly microporous carbon frameworks provide the additional benefit that the electroactive material is located within the microporous network in the form of small domains with sizes of approximately a few nanometers or less. These fine electroactive structures have lower resistance to elastic deformation and higher resistance to fracture than larger electroactive structures, and can therefore be lithiated and delithiated without excessive structural stress. Therefore, the high microporosity of the porous carbon framework not only provides improved mechanical strength of the particles, but also ensures that the electroactive material has sufficient elasticity to withstand repeated volume changes over multiple charge and discharge cycles without significant capacity loss.
[0023] Yet another factor in the extraordinary performance of the granular materials of the present invention is the minimization of SEI formation. By locating the electroactive material within small mesopores and / or micropores as described above, only a small area of the electroactive material surface is accessible to the electrolyte, thereby limiting SEI formation. Additional exposure of the electroactive material in subsequent charge-discharge cycles is largely prevented, making SEI formation not an obvious damage mechanism that may lead to capacity loss. This is in stark contrast to the excessive and unconstrained SEI formation that is characteristic of, for example, the materials disclosed by Guo (see above).
[0024] The porous carbon framework suitably comprises a three-dimensional interconnected open pore network comprising a combination of micropores and / or mesopores and optionally a small volume of macropores. According to conventional IUPAC terminology, the term "micropore" is used herein to refer to pores with a diameter less than 2 nm, the term "mesopore" is used herein to refer to pores with a diameter of 2 to 50 nm, and the term "macroporous" is used to refer to pores with a diameter greater than 50 nm.
[0025] References herein to the volumes of micropores, mesopores, and macropores in a porous carbon framework, as well as any reference to the distribution of pore volume within the porous carbon framework, refer to the internal pore volume of the porous carbon framework alone (i.e., in the absence of any electroactive material or other material occupying some or all of the pore volume).
[0026] The porous carbon framework is characterized by a high pore volume in the form of micropores and / or mesopores. The total volume of micropores and mesopores (i.e., the total pore volume in the range of 0 to 50 nm) is referred to herein as P 1 cm 3 / g, where P 1 represents a dimensionless natural number having a value of at least 0.6. More preferably, P 1 The value of is at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85. Optionally, P 1 The value of may be at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2.
[0027] The use of a high porosity carbon framework is advantageous because it enables the accommodation of larger amounts of electroactive material within the pore structure, while partitioning the pore volume into fine mesopores and micropores ensuring that the composite particles are sufficiently resistant to the compressive stresses used in conventional electrode fabrication processes.
[0028] The internal pore volume of the porous carbon framework is desirably limited to a value at which the increased fragility of the porous carbon framework outweighs the advantages of increased pore volume for accommodating larger amounts of electroactive material. 1 The value of may not exceed 2.5. However, more preferably, P 1 The value of may be no more than 2.4, or no more than 2.2, or no more than 2, or no more than 1.8, or no more than 1.6, or no more than 1.5, or no more than 1.4, or no more than 1.3, or no more than 1.2, or no more than 1.1, or no more than 1.0, or no more than 0.9. More preferably, P 1 The value of does not exceed 1.2, or does not exceed 1.1, or does not exceed 1.0, or does not exceed 0.9.
[0029] According to the present invention, P 1The value of may be, for example, in the range of 0.8 to 2.2, or in the range of 0.85 to 2.2, or in the range of 0.9 to 2.2, or in the range of 0.95 to 2.2, or in the range of 1 to 2.2, or in the range of 1.05 to 2.2, or in the range of 1.1 to 2.2, or in the range of 0.8 to 2, or in the range of 0.85 to 2, or in the range of 0.9 to 2, or in the range of 0.95 to 2, or in the range of 1 to 2, or in the range of 1.05 to 2, or in the range of 1.1 to 2, or in the range of 0.8 to 1.9, or in the range of 0.85 to 1.9, or in the range of 0.9 to 1.9, or in the range of 0.95 to 1.9, or in the range of 1 to 1.9, or in the range of 1.05 to 1.9, or in the range of 1.1 to 1.9, or in the range of 0. 8 to 1.8, or in the range of 0.85 to 1.8, or in the range of 0.9 to 1.8, or in the range of 0.95 to 1.8, or in the range of 1 to 1.8, or in the range of 1.05 to 1.8, or in the range of 1.1 to 1.8, or in the range of 0.8 to 1.7, or in the range of 0.85 to 1.7, or in the range of 0.9 to 1.7, or in the range of 0.95 to 1.7, or in the range of 1 to 1.7, or in the range of 1.05 to 1.7, or in the range of 1.1 to 1.7, or in the range of 0.8 to 1.6, or in the range of 0.85 to 1.6, or in the range of 0.9 to 1.6, or in the range of 0.95 to 1.6, or in the range of 1 to 1.6, or in the range of 1.05 to 1.6, or in the range of 1.1 to 1.6.
[0030] Preferably, the value of P1 can be, for example, in the range of 0.6 to 1.4, or in the range of 0.65 to 1.4, or in the range of 0.7 to 1.4, or in the range of 0.75 to 1.4, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0031] PD of porous carbon framework 50 The pore size does not exceed 2 nm. As used herein, the term "PD 50 The pore size is the median pore size based on the total volume of micropores and mesopores (i.e. the total volume of micropores and mesopores (measured by P 1 Thus, according to the present invention, at least 50% of the total volume of micropores and mesopores is in the form of pores having a diameter not exceeding 2 nm.
[0032] As used herein, the general term "PD n "Pore diameter" refers to the volume nth percentile pore diameter based on the total volume of micropores and mesopores. For example, as used herein, the term "D 90 The pore size is the total volume of micropores and mesopores (measured by P 1 The pore size is the pore size at which 90% of the pores are lower than a certain pore size.
[0033] For the avoidance of doubt, in order to determine the PD n value, without taking into account any macropore volume (pores larger than 50 nm).
[0034] According to the present invention, the PD of the porous carbon skeleton 50 The pore size is preferably no greater than 1.8 nm, or no greater than 1.6 nm, or no greater than 1.4 nm, or no greater than 1.2 nm, or no greater than 1 nm. 80 The pore size is at least 0.8 nm, or at least 1 nm, or at least 1.2 nm.
[0035] More preferably, at least 60% of the total micropore and mesopore volume of the porous carbon framework is in the form of pores having a diameter not exceeding 3 nm. 60 The pore diameter is preferably no greater than 3 nm, or no greater than 2.5 nm, or no greater than 2 nm, or no greater than 1.8 nm, or no greater than 1.6 nm, or no greater than 1.4 nm, or no greater than 1.2 nm.
[0036] More preferably, at least 70% of the total micropore and mesopore volume of the porous carbon framework is in the form of pores having a diameter not exceeding 3.5 nm. 70 The pore size is preferably no more than 3.5 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2.2 nm, or no more than 2 nm, or no more than 2.5 nm, or no more than 2 nm, or no more than 1.8 nm, or no more than 1.6 nm, or no more than 1.4 nm.
[0037] More preferably, at least 80% of the total micropore and mesopore volume of the porous carbon framework is in the form of pores having a diameter not exceeding 5 nm. 80 The pore size is preferably no more than 5 nm, or no more than 4.5 nm, or no more than 4 nm, or no more than 3.5 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2.2 nm, or no more than 2 nm, or no more than 1.8 nm, or no more than 1.6 nm.
[0038] The volume of the larger mesopores in the porous carbon framework is preferably confined so that the PD 90The pore diameter is no more than 10 nm, or no more than 8 nm, or no more than 6 nm, or no more than 5 nm, or no more than 4 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2 nm.
[0039] Preferably, PD 95 The pore diameter does not exceed 15 nm, or does not exceed 12 nm, or does not exceed 10 nm.
[0040] According to the present invention, the porous carbon skeleton may be one in which PD 50 No more than 2nm and PD 90 A porous carbon skeleton no larger than 10 nm, or a PD 50 No more than 2nm and PD 90 A porous carbon skeleton not exceeding 8 nm, or a PD 50 No more than 2nm and PD 90 A porous carbon skeleton not exceeding 6 nm, or a PD 50 No more than 1.8nm and PD 90 A porous carbon skeleton not exceeding 8 nm, or a PD 50 No more than 1.8nm and PD 90 A porous carbon skeleton not exceeding 6 nm, or a PD 50 No more than 1.6nm and PD 90 A porous carbon skeleton not exceeding 6 nm, or a PD 50 No more than 1.2nm and PD 90 A porous carbon skeleton not exceeding 5 nm, or a PD 50 No more than 1nm and PD 90 A porous carbon skeleton not exceeding 4 nm, or a PD 50 No more than 1nm and PD 90 A porous carbon skeleton no larger than 3 nm, or a PD 50 No more than 1nm and PD 90 A porous carbon skeleton not exceeding 2.5 nm, or a PD 50 No more than 1nm and PD 90 Porous carbon skeleton no larger than 2nm.
[0041] More preferably, the porous carbon framework may be one in which PD 50 1 to 2 nm and PD 90 A porous carbon framework of 3 to 10 nm, or a PD 50 1 to 2 nm and PD 90 A porous carbon framework of 3 to 8 nm, or a PD 50 1 to 2 nm and PD 90 A porous carbon framework of 3 to 6 nm, or a PD50 1 to 1.8 nm and PD 90 A porous carbon framework of 3 to 8 nm, or a PD 50 1 to 1.8 nm and PD 90 A porous carbon framework of 3 to 6 nm, or a PD 50 1 to 1.6 nm and PD 90 It is a porous carbon skeleton with a diameter of 3 to 6 nm.
[0042] A small portion of pores with diameters in the larger mesoporous range can advantageously facilitate access of the electrolyte to the electroactive material. Thus, pores with diameters in the range of 5 to 50 nm (i.e., larger mesopores) can optionally constitute at least 1%, at least 2%, at least 5%, or at least 10% of the total micropore and mesopore volume of the porous carbon framework.
[0043] The volume ratio of micropores to mesopores in the porous carbon skeleton may be substantially in the range of 100:0 to 50:50. Preferably, the volume ratio of micropores to mesopores is 90:10 to 55:45, or 90:10 to 60:40, or 85:15 to 65:35.
[0044] The pore size distribution of the porous carbon framework can be unimodal, bimodal or multimodal. As used herein, the term "pore size distribution" relates to the distribution of the pore size of the porous carbon framework relative to the cumulative total internal pore volume. Bimodal or multimodal pore size distributions may be preferred because the close proximity between pores with a diameter of up to 5 nm and pores with larger diameters provides the advantage of efficient ion transport from the porous network to the electroactive material. Therefore, the particulate material has high ion diffusivity and thus improved rate performance.
[0045] Optionally, the porous carbon skeleton has a bimodal or multimodal pore size distribution, the bimodal or multimodal pore size distribution includes at least one peak at less than 2nm and at least one peak in the range of 2.5 to 20nm, preferably the local minimum in the pore size distribution is in the range of 2 to 50nm. More preferably, the porous carbon skeleton has a bimodal or multimodal pore size distribution, the bimodal or multimodal pore size distribution includes at least one peak at less than 2nm and at least one peak in the range of 2.5 to 15nm, preferably the local minimum in the pore size distribution is in the range of 2 to 5nm.
[0046] Suitably, the bimodal or multimodal pore size distribution comprises a peak pore size in the micropore range and a peak pore size in the mesopore size range, which differ from each other by a factor of 5 to 20, more preferably by a factor of about 10. For example, the porous carbon framework may have a bimodal pore size distribution comprising a peak at a pore size of 1.2 nm and a peak at a pore size of 12 nm.
[0047] According to the method described in ISO 15901-2 and ISO 15901-3, nitrogen adsorption was performed at 77K down to 10 -6 The relative pressure p / p0 of quenched solid density functional theory (QSDFT) is used to determine the total volume of micropores and mesopores and the pore size distribution of micropores and mesopores. Nitrogen adsorption is a technique for characterizing the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure increases, the gas first condenses in the pores with the smallest diameter, and the pressure increases until a saturation point is reached, at which all pores are filled with liquid. The nitrogen pressure is then gradually reduced to evaporate the liquid from the system. Analysis of the adsorption and desorption isotherms and the hysteresis between them enables the determination of pore volume and pore size distribution. Suitable instruments for measuring pore volume and pore size distribution by nitrogen adsorption include TriStar II and TriStar IIPlus porosity analyzers (which can be obtained by Micromeritics Instrument Corporation in the United States), and Autosorb IQ porosity analyzers (which can be obtained by Quantachrome Instruments).
[0048] Nitrogen adsorption is effective for measuring the pore volume and pore size distribution of pores with a diameter of up to 50 nm, but is less reliable for pores with much larger diameters. For the purposes of the present invention, therefore, only pores with a diameter of up to 50 nm (including 50 nm) are used to determine the pore volume and pore size distribution. As described above, P is determined by considering only pores with a diameter of up to 50 nm (including 50 nm) (i.e., only micropores and mesopores). 1 The value of PD is also determined relative to the total volume of micropores and mesopores alone. n The value of .
[0049] Given the limitations of available analytical techniques, it is not possible to measure the pore volume and pore size distribution over the entire range of micropores, mesopores, and macropores using a single technique. In the case where the porous carbon framework includes macropores, the volume of pores in the range of greater than 50 nm to a maximum of 100 nm is considered herein to have a value of P. 2 cm 3 / g, and is measured by mercury intrusion porosimetry. As described above, P 2 The value of relates to the pore volume of the porous carbon framework alone, (ie, the pore volume of the porous carbon framework in the absence of any electroactive material or other material occupying some or all of the pore volume).
[0050] For the avoidance of doubt, P 2The value of takes into account only pores with diameters from greater than 50 nm up to and including 100 nm, i.e. it includes only the volume of macropores with a diameter of up to 100 nm. 2 The value of P is not taken into account for any pore volume below 50 nm as measured by mercury intrusion (as described above, nitrogen adsorption is used instead to characterize mesopores and micropores). For the purposes of this invention, the pore volume above 100 nm as measured by mercury intrusion is assumed to be the interparticle porosity and is not used in determining P. 2 The value of is not considered.
[0051] Mercury intrusion porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying varying levels of pressure to a sample of the material immersed in mercury. The pressure required to cause mercury to penetrate into the pores of the sample is inversely proportional to the size of the pores. The values obtained by mercury intrusion porosimetry reported herein are obtained according to ASTM UOP578-11, where for mercury at room temperature, the surface tension γ is 480 mN / m and the contact angle is is 140°. The density of mercury at room temperature is 13.5462 g / cm 3 A variety of high precision mercury porosimetry instruments are commercially available, such as the AutoPore IV series of automated mercury porosimeters, available from Micromeritics Instrument Corporation in the United States. For a complete overview of mercury porosimetry, reference may be made to PA Webb and C. Orr, "Analytical Methods in Fine Particle Technology", 1997, Micromeritics Instrument Corporation, ISBN 0-9656783-0.
[0052] The volume of macropores is preferably small compared to the volume of micropores and mesopores. Although a small portion of macropores may be useful in facilitating entry of electrolyte into the pore network, the advantages of the present invention are substantially obtained by accommodating the pore volume primarily in micropores and smaller mesopores.
[0053] Therefore, according to the present invention, the total volume of the macropores in the porous carbon framework measured by mercury intrusion porosimetry is P 2 cm 3 / g, where P 2 The value of P is preferably no more than 0.2×P 1 , or not more than 0.1×P 1 , or not more than 0.05×P 1 , or not more than 0.02×P 1 , or not more than 0.01×P 1, or not more than 0.005×P 1 .
[0054] In a preferred embodiment, P 2 The value of does not exceed 0.3, or does not exceed 0.25, or does not exceed 0.20, or does not exceed 0.15, or does not exceed 0.1, or does not exceed 0.05. As discussed above with respect to larger mesopores, a small pore volume fraction in the macropore range can advantageously facilitate access of the electrolyte to the electroactive material.
[0055] The open pore network optionally comprises a hierarchical pore structure, ie, a pore structure in which there is a degree of pore size ordering, with smaller pores branching from larger pores.
[0056] It should be understood that intrusion techniques such as gas adsorption and mercury intrusion are only effective for determining the pore volume of pores accessible to nitrogen or mercury from outside the porous carbon framework. The porosity values (P) as specified herein are 1 and P 2 ) should be understood to refer to the volume of open pores (pores accessible to fluid from outside the porous carbon framework). In this article, when specifying porosity values, completely enclosed pores that cannot be identified by nitrogen adsorption or mercury intrusion should not be taken into account. Similarly, for determining P 1 The value of is 0.01, nor does it take into account any pore volume located in pores so small as to be below the detection limit for nitrogen adsorption.
[0057] As used herein, the term "particle size" refers to the equivalent spherical diameter (esd), which is the diameter of a sphere having the same volume as a given particle, wherein the particle volume is understood to include the volume of any intraparticle pores. As used herein, the term "D 50 ” and “D 50 The term "particle size" as used herein refers to the volume median particle size, i.e., the diameter below which 50% of the volume of the particle population is measured. 10 ” and “D 10 The term "particle size" as used herein refers to the 10th percentile volume median particle size, i.e., the diameter at which 10% of the volume of the particle population is below a certain diameter. 90 ” and “D 90 The term "particle size" refers to the 90th percentile volume median particle size, i.e., the diameter below which 90% of the volume of the particle population is measured.
[0058] The term "D" used herein to define particle size distribution should be n ” is used in this document to define the pore size distribution as described above. n " to distinguish.
[0059] Particle size and particle size distribution can be determined by conventional laser diffraction techniques according to ISO 13320:2009. Laser diffraction relies on the principle that particles will scatter light at an angle that varies depending on the size of the particle, and that multiple particles will produce a scattered light pattern defined by intensity and angle that can be related to the particle size distribution. A variety of laser diffraction instruments are commercially available for rapid and reliable determination of particle size distribution. Unless otherwise stated, particle size distribution measurements indicated or reported herein were made by conventional Malvern Mastersizer from Malvern Instruments. TM Measured by Malvern Mastersizer 3000 particle size analyzer. TM The 3000 particle size analyzer operates by projecting a helium-neon gas laser beam through a transparent pool containing particles of interest suspended in an aqueous solution. The light that impinges on the particles is scattered through an angle inversely proportional to the particle size, and a photodetector array measures the intensity of the light at multiple predetermined angles, and the intensity measured at different angles is processed by a computer using standard theoretical principles to determine the particle size distribution. The laser diffraction values reported herein are obtained using a wet dispersion of particles in distilled water. The particle refractive index is 3.50, and the dispersant index is 1.330. The particle size distribution is calculated using the Mie scattering model.
[0060] D of composite particles 90 The particle size is preferably no more than 9.5 μm, or no more than 9 μm, or no more than 8.5 μm, or no more than 8 μm, or no more than 7.5 μm, or no more than 7 μm, or no more than 6.5 μm, or no more than 6 μm, or no more than 5.5 μm, or no more than 5 μm, or no more than 4.5 μm, or no more than 4 μm.
[0061] D of composite particles 50 The particle size may be in the range of 0.5 to 7 μm. Optionally, the D 50 The particle size may be at least 1 μm, or at least 1.5 μm, or at least 2 μm, or at least 2.5 μm, or at least 3 μm.
[0062] Optionally, the D of the composite particles 50 The particle size may be no greater than 6.5 μm, or no greater than 6 μm, or no greater than 5.5 μm, or no greater than 5 μm, or no greater than 4.5 μm, or no greater than 4 μm, or no greater than 3.5 μm.
[0063] For example, the D of a composite particle 50The particle size may be in the range of 1 to 6.5 μm, or 1.5 to 6 μm, or 2 to 5.5 μm, or 2.5 to 5 μm, or 3 to 4.5 μm. Particles within these size ranges and having the porosity and pore size distribution described herein are ideally suited for use in anodes of metal ion batteries due to their dispersibility in slurries, their structural robustness, their capacity retention with repeated charge-discharge cycles, and their suitability for forming dense electrode layers of uniform thickness without structural degradation.
[0064] D of composite particles 10 The particle size is preferably at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 The particle size is maintained above 0.2 μm, reducing the possibility of undesirable agglomeration of submicron sized particles, resulting in improved dispersion of the particulate material and improved capacity retention.
[0065] D of composite particles 99 The particle size is preferably no more than 25 μm, or no more than 20 μm, or no more than 18 μm, or no more than 15 μm, or no more than 12 μm, or no more than 10 μm, or no more than 9 μm, or no more than 8 μm, or no more than 7 μm, or no more than 6 μm, or no more than 5 μm.
[0066] The particle size preferably has a positive skew in the volume-based distribution, i.e., such that the volume-based distribution is asymmetric with a longer tail on the right hand side. A positive skew in the volume-based particle size distribution is advantageous because it provides a denser electrode since the natural filling factor will be higher than if all particles were the same size, thereby reducing the need for calendaring or other physical densification processes.
[0067] The composite particles preferably have a narrow size distribution span. For example, the particle size distribution span (defined as (D 90 -D 10 ) / D 50 ) is preferably no more than 8, and may optionally be 5 or less, or 4 or less, or 3 or less. Preferably, the particle size distribution span is at least 1, and may optionally be at least 1.5, or at least 2.
[0068] The shape of the composite particles is preferably spherical. Spherical particles as defined herein may include both spherical particles and ellipsoidal particles, and the shape of the composite particles of the present invention may be suitably defined with reference to the sphericity and aspect ratio of the particles of the present invention. It was found that spherical particles are particularly well suited for dispersion in slurry without forming agglomerates. In addition, it was unexpectedly found that the use of porous spherical particles provides a further improvement in strength when compared to porous particles and porous particle fragments of irregular morphology.
[0069] The sphericity of an object is conventionally defined as the ratio of the surface area of a sphere to the surface area of an object, wherein the object and the sphere have the same volume. However, it is actually difficult to measure the surface area and volume of individual particles at micrometer scale. However, highly accurate two-dimensional projections of micrometer-scale particles can be obtained by scanning electron microscopy (SEM) and by dynamic image analysis, wherein a digital camera is used to record the shadows projected by the particles. The term "sphericity" as used herein should be understood as the ratio of the area of a particle projection to the area of a circle, wherein the particle projection and the circle have the same perimeter. Therefore, for individual particles, the sphericity S can be defined as:
[0070]
[0071] Among them A m is the measured area of the particle projection, and C m is the measured circumference of the particle projection. As used herein, the average sphericity S of a plurality of particles av is defined as:
[0072]
[0073] Where n represents the number of particles in the population.
[0074] As used herein, the term "quasi-spherical" as applied to the composite particles of the present invention is understood to refer to materials having an average sphericity of at least 0.70. The average sphericity of the porous particles of the present invention is preferably at least 0.85, or at least 0.90, or at least 0.92, or at least 0.93, or at least 0.94, or at least 0.95. Optionally, the average sphericity of the porous quasi-spherical particles can be at least 0.96, or at least 0.97, or at least 0.98, or at least 0.99.
[0075] Preferably, a sphericity within these preferred ranges is combined with a positive skewness in the volume-based particle size distribution to obtain optimal packing of the particles into a dense electrode layer while reducing the need for physical densification (eg, by calendering).
[0076] It is to be understood that in the case of any particles that are not perfectly spherical, the perimeter and area of the two-dimensional particle projection will depend on the orientation of the particle. However, the effect of particle orientation can be offset by reporting the sphericity and aspect ratio as average values obtained for multiple particles with random orientation. A variety of SEM and dynamic image analysis instruments are commercially available, enabling the sphericity and aspect ratio of particulate materials to be determined quickly and reliably. Unless otherwise stated, the sphericity values as specified or reported herein are measured by a CamSizer XT particle analyzer from Retsch Technology GmbH. CamSizer XT is a dynamic image analysis instrument that is capable of obtaining highly accurate distributions of the size and shape of particulate materials with sample volumes of 100 mg to 100 g, enabling properties such as average sphericity and aspect ratio to be calculated directly by the instrument.
[0077] The porous carbon framework may comprise crystalline carbon or amorphous carbon, or a mixture of amorphous carbon and crystalline carbon.The porous carbon framework may be a hard carbon or a soft carbon framework, and may be suitably obtained by known procedures involving pyrolysis of polymers.
[0078] As used herein, the term "hard carbon" refers to carbon atoms found predominantly as sp in nanoscale polyaromatic domains. 2 A disordered carbon matrix in a hybrid state (triple bonds). The polyaromatic domains are cross-linked using chemical bonds such as C-O-C bonds. Due to the chemical cross-linking between the polyaromatic domains, hard carbon cannot be converted into graphite at high temperatures. Hard carbon has graphite-like properties, which is demonstrated by a large G band (~1600 cm-1) in the Raman spectrum. However, the carbon is not completely graphitic, which is demonstrated by a significant D band (~1350 cm-1) in the Raman spectrum.
[0079] As used herein, the term "soft carbon" also refers to polyaromatic domains in which carbon atoms are found predominantly in sp 2 The polyaromatic domains in soft carbon are associated by intermolecular forces rather than crosslinked by chemical bonds, as in hard carbon. This means that they will graphitize at high temperatures. The porous carbon framework preferably contains at least 50% sp 2 Hybridized carbon (measured by XPS). For example, the porous carbon framework may suitably contain 50% to 98% sp 2 Hybridized carbon, 55% to 95% sp 2 Hybridized carbon, 60% to 90% sp 2 Hybridized carbon, or 70% to 85% sp 2 Hybridized carbon.
[0080] A wide variety of different materials can be used to prepare suitable porous carbon skeletons. Examples of organic materials that can be used include: plant biomass, which includes lignocellulosic materials (such as coconut shells, rice husks, wood, etc.), and fossil carbon sources, such as coal. Examples of polymer materials that form porous carbon skeletons during pyrolysis include: phenolic resins, novolac resins, asphalt, melamine, polyacrylates, polystyrene, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), and various copolymers containing monomer units of acrylates, styrene, α-olefins, vinyl pyrrolidone and other ethylenically unsaturated monomers. Depending on the raw materials and conditions of the pyrolysis process, a variety of hard carbon materials are available in the art.
[0081] The porous carbon framework may be subjected to a chemical or gas activation process to increase the volume of the mesopores and micropores. Suitable activation processes include contacting the pyrolytic carbon with one or more of oxygen, water vapor, CO, CO2, and KOH at a temperature in the range of 600 to 1000°C.
[0082] Mesopores can also be obtained by known templating processes using removable pore formers such as MgO and other colloidal or polymer templates that can be removed by thermal or chemical means after pyrolysis or activation.
[0083] The BET surface area of the porous carbon framework is preferably at least 750 m 2 / g, or at least 1,000m 2 / g, or at least 1,250m 2 / g, or at least 1,500m 2 / g. As used herein, the term "BET surface area" should be considered to mean the surface area per unit mass calculated from the measurement results of the physical adsorption of gas molecules on the solid surface using the Brunauer-Emmett-Teller principle according to ISO 9277. Preferably, the BET surface area of the conductive porous particle skeleton does not exceed 4,000 m 2 / g, or not more than 3,500m 2 / g, or not more than 3,250m 2 / g, or not more than 3,000m 2 / g. In some cases, the particulate materials of the present invention may include pores in which the completely encapsulated void space is capped by the electroactive material, thereby preventing the electrolyte from entering the void space.
[0084] The electroactive material is suitably selected from silicon, tin, germanium and aluminum and mixtures thereof. The preferred electroactive material is silicon. The electroactive material may optionally contain a small amount of one or more dopants. Suitable dopants include boron and phosphorus, other n-type or p-type dopants or nitrogen. Preferably, the dopant is present in a total amount of no more than 2% by weight based on the total amount of the electroactive material (e.g. silicon) and the one or more dopants.
[0085] The amount of electroactive material in the composite particles of the present invention is preferably selected so that no more than about 55% of the internal pore volume of the porous carbon framework is occupied by the electroactive material (in the uncharged state). This is referred to herein as the "filling factor" of the electroactive material within the porous carbon framework. Preferably, the electroactive material occupies about 25% to about 45% of the internal pore volume of the porous carbon framework, more preferably about 25% to 40% of the internal pore volume of the porous carbon framework. Within these preferred ranges, the pore volume of the porous carbon framework effectively accommodates the expansion of the electroactive material during charge and discharge, but avoids excessive pore volume, which is not conducive to the volumetric capacity of the particle material. However, the amount of electroactive material is not so high as to hinder effective lithiation due to mechanical resistance to lithiation caused by insufficient metal ion diffusion rate or insufficient expansion volume.
[0086] The weight ratio of the electroactive material to the porous carbon skeleton can be determined by elemental analysis. Elemental analysis is used to determine the weight percentage of both the electroactive material and the carbon in the composite particles. Optionally, the amount of hydrogen, nitrogen and oxygen can also be determined by elemental analysis. Preferably, elemental analysis is also used to determine the weight percentage of carbon (and optional hydrogen, nitrogen and oxygen) in a separate porous carbon skeleton. Determining the weight percentage of carbon in a separate porous carbon skeleton takes into account the possibility that the porous carbon skeleton contains a small amount of heteroatoms within its molecular skeleton. The two measurements performed together make it possible to reliably determine the weight percentage of the electroactive material relative to the entire porous carbon skeleton.
[0087] The weight percentage of electroactive materials (such as silicon, germanium, tin and aluminum) is preferably determined by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy). A variety of ICP-OES instruments are commercially available, such as The carbon content (and, if desired, the hydrogen content, nitrogen content and oxygen content) of the composite particles and the individual porous carbon frameworks is preferably determined by IR absorption. A suitable instrument for determining the carbon content, hydrogen content, nitrogen content and oxygen content is Micro Elemental Analyzer (available from Leco Corporation).
[0088] The weight ratio of electroactive material to porous carbon framework is a function of the available pore volume, the desired filling factor, and the density of the electroactive material.
[0089] In the case where the electroactive material is silicon, the weight ratio of silicon to the porous carbon framework is preferably [0.5×P 1 to 1.7×P 1 ]:1, where P 1 Indicated in cm 3 / g measured total micropore / mesopore volume. 1 The weight ratio of silicon to the porous carbon skeleton is controlled within a specific range. In other words, when the weight ratio of silicon to the porous carbon skeleton is within [0.5×P 1 to 1.7×P 1 ]:1, the volume of silicon in the composite particles is equivalent to approximately 20% to 55% of the total micropore / mesopore volume of the porous carbon framework.
[0090] Optionally, the weight ratio of silicon to the porous carbon framework may be in the range of [0.5×P 1 To 1.3×P 1 More preferably, the weight ratio of silicon to the porous carbon skeleton is in the range of [0.55×P 1 To 1.1×P 1 ]:1, or in the range of [0.6×P 1 To 1.1×P 1 ]:1, or in the range of [0.6×P 1 To 1×P 1 ]:1, or in the range of [0.6×P 1 To 0.95×P 1 ]:1, or in the range of [0.6×P 1 To 0.9×P 1 ]:1, or in the range of [0.65×P 1 To 0.9×P 1 ]:1, or in the range of [0.65×P 1 To 0.85×P 1 ]:1, or in the range of [0.65×P 1 To 0.8×P 1 ]:1, or in the range of [0.7×P 1 To 0.8×P 1 ]:1.
[0091] Optionally, the weight ratio of silicon to the porous carbon framework can be in the range of [1×P 1 to 1.7×P 1 More preferably, the weight ratio of silicon to the porous carbon skeleton is in the range of [1.1×P1 to 1.7×P 1 ]:1, or in the range of [1.1×P 1 to 1.65×P 1 ]:1, or in the range of [1.1×P 1 To 1.6×P 1 ]:1, or in the range of [1.15×P 1 To 1.6×P 1 ]:1, or in the range of [1.15×P 1 To 1.55×P 1 ]:1, or in the range of [1.15×P 1 To 1.5×P 1 ]:1, or in the range of [1.2×P 1 To 1.5×P 1 ]:1, or in the range of [1.25×P 1 To 1.5×P 1 ]:1, or in the range of [1.3×P 1 To 1.5×P 1 ]:1.
[0092] The mass of the electroactive material in the composite particles is preferably at least 90 weight percent, more preferably at least 95 weight percent, and even more preferably at least 98 weight percent located within the internal pore volume of the porous carbon framework, so that no or very little electroactive material is located on the outer surface of the composite particles.
[0093] The particulate materials of the present invention may be further characterized by their performance under thermogravimetric analysis (TGA) in air. Preferably, no more than 10%, more preferably no more than 5%, more preferably no more than 2% of the silicon content in the particulate material is not oxidized at 800°C when the particulate material is analyzed by TGA in air at a heating rate of 10°C / min.
[0094] The amount of unoxidized silicon was determined from characteristic TGA traces of these materials. The mass increase at about 300-500° C. corresponds to the initial oxidation of silicon to SiO2, followed by a mass loss at about 500-600° C. as carbon is oxidized to CO2 gas. Above about 600° C., there is a further mass increase corresponding to the continued conversion of silicon to SiO2, increasing to an asymptotic value above 1000° C. as silicon oxidation is completed.
[0095] For the purposes of this analysis, it is assumed that any mass increase above 800°C corresponds to oxidation of silicon to SiO2, and that the total mass at the completion of oxidation is SiO2. This enables the percentage of silicon that is not oxidized at 800°C to be determined (as a proportion of the total amount of silicon) according to the following formula:
[0096] Z=1.875×[(M f -M 800 ) / M f ]×100%
[0097] Where Z is the percentage of silicon that is not oxidized at 800°C, M f is the mass of the sample at the completion of oxidation, and M 800 is the mass of the sample at 800 °C.
[0098] Without being bound by theory, it is understood that the temperature at which silicon is oxidized under TGA corresponds roughly to the length scale of the oxide coating on the silicon, because the oxygen atoms diffuse through the oxide layer and are thermally activated. The size of the silicon nanostructures and their location limit the length scale of the oxide coating thickness. Therefore, it is understood that silicon deposited in micropores and mesopores will oxidize at lower temperatures than silicon deposits on the particle surface because there is a necessarily thinner oxide coating on these structures. Therefore, the preferred materials according to the present invention exhibit essentially complete oxidation of silicon at low temperatures, which is consistent with the small length scale of the silicon nanostructures located in the micropores and smaller mesopores. For the purposes of the present invention, silicon oxidation at 800°C is assumed to be silicon on the outer surface of the porous carbon skeleton.
[0099] The silicon is preferably amorphous silicon. Amorphous silicon is believed to have better properties as an electrically active material. The morphology of the silicon can be determined using X-ray diffraction (XRD) by known procedures.
[0100] Preferably, the volume of micropores and mesopores in the composite particles (ie in the presence of the electroactive material) measured by nitrogen adsorption does not exceed 0.15 x P 1 , or not more than 0.10x P 1 , or not more than 0.05x P 1 , or not more than 0.02xP 1 .
[0101] The composite particles preferably have a low total oxygen content. Oxygen may be present in the composite particles, for example, as part of the porous carbon framework or as an oxide layer on any exposed electroactive material surface. Preferably, the total oxygen content of the composite particles is less than 15 wt%, more preferably less than 10 wt%, more preferably less than 5 wt%, for example less than 2 wt%, or less than 1 wt%, or less than 0.5 wt%.
[0102] The BET surface area of the granular material of the present invention is preferably not more than 300 m 2 / g, or not more than 250m 2 / g, or not more than 200m 2 / g, or not more than 150m 2 / g, or not more than 100m 2 / g, or not more than 80m 2 / g, or not more than 60m 2 / g, or not more than 40m 2 / g, or not more than 30m 2 / g, or not more than 25m 2 / g, or not more than 20m 2 / g, or not more than 15m 2 / g, or not more than 10m 2 / g. Generally, a low BET surface area is preferred to minimize the formation of a solid electrolyte interface (SEI) layer at the surface of the composite particles during the first charge-discharge cycle of an anode comprising the particulate material of the present invention. However, too low a BET surface area results in unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to the metal ions in the surrounding electrolyte. For example, the BET surface area is preferably at least 0.1 m 2 / g, or at least 1m 2 / g, or at least 2m 2 / g, or at least 5m 2 / g. For example, the BET surface area can be 2 / g to 25m 2 / g, more preferably in the range of 2 to 15 m 2 / g range.
[0103] The particle material of the present invention has a specific charge capacity of 1200 to 2340 mAh / g upon first lithiation. Preferably, the particle material of the present invention has a specific charge capacity of at least 1400 mAh / g upon first lithiation.
[0104] The composite particles of the present invention are suitably prepared by chemical vapor infiltration (CVI) of a silicon-containing precursor into the pore structure of a porous carbon framework. As used herein, CVI refers to a process in which a gaseous silicon-containing gas is thermally decomposed on a surface to form elemental silicon and gaseous byproducts at the surface.
[0105] Suitable gaseous silicon-containing precursors include silane (SiH4), silane derivatives (e.g., disilane, trisilane and tetrasilane) and trichlorosilane (SiHCl3). The silicon-containing precursor can be used in pure form, or more generally as a mixture diluted with an inert carrier gas such as nitrogen or argon. For example, the silicon-containing precursor can be used in an amount ranging from 0.5 to 20 volume %, or 1 to 10 volume % or 1 to 5 volume % based on the total volume of the silicon-containing precursor and the inert carrier. The CVI process is suitably carried out with a low silicon precursor partial pressure at a total pressure of 101.3 kPa (i.e., 1 atm), and the remaining partial pressure is supplemented to atmospheric pressure using an inert filler gas such as hydrogen, nitrogen or argon. A deposition temperature in the range of 400 to 700°C is used, for example, 400 to 550°C, or 400 to 500°C, or 400 to 450°C or 450 to 500°C. The CVI process may suitably be carried out in a fixed bed reactor, a fluidised bed reactor (including a spouted bed reactor) or a rotary kiln.
[0106] As an example of a fixed bed reactor method, 1.8g of porous skeleton of particles is placed on a stainless steel plate along its length with a constant thickness of 1mm. The plate is then placed in a stainless steel tube with an outer diameter of 60mm with a gas inlet and outlet pipeline in the hot zone of a retort furnace. The furnace tube is purged with nitrogen for 30 minutes at room temperature, and then the sample temperature is raised to 450 to 500°C. The nitrogen flow rate is adjusted to ensure a gas residence time of at least 90 seconds in the furnace tube, and the nitrogen flow rate is maintained at this rate for 30 minutes. Then, the gas supply is switched from nitrogen to a mixture of monosilane in nitrogen at a concentration of 1.25% by volume. The feeding of monosilane is carried out in a period of 5 hours when the reactor pressure is maintained at 101.3kPa (1atm). After the feeding is completed, the gas flow rate is kept constant while purging silane from the furnace with nitrogen. The furnace is purged under nitrogen for 30 minutes and then cooled to room temperature within a few hours. The atmosphere was then gradually switched to air over a two hour period by switching the gas flow from nitrogen to air from a compressed air supply.
[0107] The granular material of the present invention may optionally include a conductive carbon coating. Suitably, the conductive carbon coating may be obtained by chemical vapor deposition (CVD). CVD is a method well known in the art and includes thermally decomposing a volatile carbon-containing gas (e.g., ethylene) onto the surface of the granular material. Alternatively, the carbon coating may be formed by depositing a solution of a carbon-containing compound onto the surface of the granular material and then thermally decomposing it. The conductive carbon coating has sufficient permeability to allow lithium to approach the interior of the composite particles without excessive resistance, thereby not reducing the rate performance of the composite particles. For example, the thickness of the carbon coating may suitably be in the range of 2 to 30 nm. Optionally, the carbon coating may be porous, and / or may only partially cover the surface of the composite particles.
[0108] The carbon coating has the following advantages: it further reduces the BET surface area of the particle material by smoothing any surface defects and by filling any remaining surface micropores, thereby further reducing first cycle losses. In addition, the carbon coating increases the conductivity of the surface of the composite particles, thereby reducing the need for conductive additives in the electrode composition, and also creates an optimal surface for the formation of a stable SEI layer, resulting in improved capacity retention during cycling.
[0109] According to the first aspect of the present invention, there is also provided a granular material according to the following aspects 1-1 to 1-16.
[0110] Aspect 1-1: The granular material according to the first aspect of the present invention, wherein:
[0111] (i)P 1 In the range of 0.6 to 1.4;
[0112] (ii)PD 50 The pore diameter ranges from 0.8 to 2 nm;
[0113] (iii) D of porous carbon framework 50 The particle size ranges from 1 to 18 μm.
[0114] Aspect 1-2: The granular material according to the first aspect of the present invention, wherein:
[0115] (i)P 1 In the range of 0.6 to 1.4;
[0116] (ii)PD 50 The pore diameter ranges from 0.8 to 2 nm;
[0117] (iii) D of porous carbon framework 50 The particle size ranges from 1 to 12 μm.
[0118] Aspect 1-3: The granular material according to the first aspect of the present invention, wherein:
[0119] (i)P 1 In the range of 0.6 to 1.4;
[0120] (ii)PD 50 The pore diameter ranges from 0.8 to 2 nm;
[0121] (iii) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm.
[0122] Aspects 1-4: The granular material according to the first aspect of the present invention, wherein:
[0123] (i)P 1 In the range of 0.6 to 1.4;
[0124] (ii)PD 50 The pore diameter ranges from 0.8 to 2 nm;
[0125] (iii) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm.
[0126] Aspects 1-5: The granular material according to the first aspect of the present invention, wherein:
[0127] (i)P 1 In the range of 0.7 to 1.2;
[0128] (ii)PD 50 The pore size is in the range of 1 to 2 nm;
[0129] (iii) D of porous carbon framework 50 The particle size ranges from 1 to 18 μm.
[0130] Aspects 1-6: The granular material according to the first aspect of the present invention, wherein:
[0131] (i)P 1 In the range of 0.7 to 1.2;
[0132] (ii)PD 50 The pore size is in the range of 1 to 2 nm;
[0133] (iii) D of porous carbon framework 50 The particle size ranges from 1 to 12 μm.
[0134] Aspects 1-7: The granular material according to the first aspect of the present invention, wherein:
[0135] (i)P 1 In the range of 0.7 to 1.2;
[0136] (ii)PD 50 The pore size is in the range of 1 to 2 nm;
[0137] (iii) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm.
[0138] Aspects 1-8: The granular material according to the first aspect of the present invention, wherein:
[0139] (i)P 1 In the range of 0.7 to 1.2;
[0140] (ii)PD 50The pore size is in the range of 1 to 2 nm;
[0141] (iii) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm.
[0142] Aspects 1-9: The granular material according to the first aspect of the present invention, wherein:
[0143] (i)P 1 in the range of 0.7 to 1;
[0144] (ii)PD 50 The pore diameter is in the range of 1.2 to 2 nm;
[0145] (iii) D of porous carbon framework 50 The particle size ranges from 1 to 18 μm.
[0146] Aspects 1-10: The granular material according to the first aspect of the present invention, wherein:
[0147] (i)P 1 in the range of 0.7 to 1;
[0148] (ii)PD 50 The pore diameter is in the range of 1.2 to 2 nm;
[0149] (iii) D of porous carbon framework 50 The particle size ranges from 1 to 12 μm.
[0150] Aspects 1-11: The granular material according to the first aspect of the present invention, wherein:
[0151] (i)P 1 in the range of 0.7 to 1;
[0152] (ii)PD 50 The pore diameter is in the range of 1.2 to 2 nm;
[0153] (iii) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm.
[0154] Aspects 1-12: The granular material according to the first aspect of the present invention, wherein:
[0155] (i)P 1 in the range of 0.7 to 1;
[0156] (ii)PD 50 The pore diameter is in the range of 1.2 to 2 nm;
[0157] (iii) D of porous carbon framework 50The particle size ranges from 3 to 6 μm.
[0158] Aspects 1-13: The granular material according to the first aspect of the present invention, wherein:
[0159] (i)P 1 in the range of 0.7 to 1;
[0160] (ii)PD 50 The pore diameter ranges from 1.2 to 1.8 nm;
[0161] (iii) D of porous carbon framework 50 The particle size ranges from 1 to 18 μm.
[0162] Aspects 1-14: The granular material according to the first aspect of the present invention, wherein:
[0163] (i)P 1 in the range of 0.7 to 1;
[0164] (ii)PD 50 The pore diameter ranges from 1.2 to 1.8 nm;
[0165] (iii) D of porous carbon framework 50 Particle size ranges from 1 to 12 μm;
[0166] Aspects 1-15: The granular material according to the first aspect of the present invention, wherein:
[0167] (i)P 1 in the range of 0.7 to 1;
[0168] (ii)PD 50 The pore diameter ranges from 1.2 to 1.8 nm;
[0169] (iii) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;
[0170] Aspects 1-16: The granular material according to the first aspect of the present invention, wherein:
[0171] (i)P 1 in the range of 0.7 to 1;
[0172] (ii)PD 50 The pore diameter ranges from 1.2 to 1.8 nm;
[0173] (iii) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm;
[0174] According to the present invention, it should be understood that the preferred / optional features disclosed herein in relation to the first aspect of the present invention within the scope of the above-mentioned aspects 1-1 to 1-16 are also considered to be the preferred / optional features of aspects 1-1 to 1-16. Likewise, any features of the dependent claims within the scope of the above-mentioned aspects 1-1 to 1-16 should also be interpreted as if those claims also depend on aspects 1-1 to 1-16.
[0175] In the second aspect of the present invention, a composition comprising a granular material according to the first aspect of the present invention and at least one other component is provided. The granular material used to prepare the composition of the second aspect of the present invention may have any of the features described as preferred or optional with respect to the first aspect of the present invention, and may be a granular material according to any one of aspects 1-1 to 1-16. Specifically, the granular material of the first aspect of the present invention may be used as a component of an electrode composition.
[0176] Thus, there is provided a composition comprising a particulate material according to the first aspect of the invention and at least one further component selected from: (i) a binder; (ii) a conductive additive; and (iii) a further particulate electroactive material. The composition of the invention can be used as an electrode composition and can therefore be used to form an active layer of an electrode.
[0177] The electrode composition may optionally be a hybrid electrode composition comprising the particulate material according to the first aspect of the invention and at least one additional particulate electroactive material. Examples of additional particulate electroactive materials include graphite, hard carbon, silicon, germanium, gallium, aluminum and lead. The at least one additional particulate electroactive material is preferably selected from graphite and hard carbon, and most preferably, the at least one additional particulate electroactive material is graphite.
[0178] The granular material of the present invention can account for 0.5 to 99.5 weight % of the total dry weight of the electrode composition (i.e., the total dry weight of the granular material of the present invention and any additional granular electroactive materials, binders and / or conductive additives). More preferably, the electrode composition comprises a high loading of the granular material of the present invention. For example, the granular material of the present invention can preferably account for at least 50 weight % or at least 55 weight % or at least 60 weight % or at least 65 weight % or at least 70 weight % or at least 75 weight % or at least 80 weight % or at least 85 weight % or at least 90 weight % or at least 95 weight % of the total dry weight of the electrode composition.
[0179] The electrode composition may optionally include a binder. The binder serves to adhere the electrode composition to the current collector and maintain the integrity of the electrode composition. Examples of binders that can be used according to the present invention include polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, carboxymethyl cellulose (CMC), modified carboxymethyl cellulose (mCMC), sodium carboxymethyl cellulose (Na-CMC), polyvinyl alcohol (PVA), alginate and its alkali metal salts, styrene-butadiene rubber (SBR) and polyimide. The electrode composition may include a mixture of multiple binders. Preferably, the binder includes a polymer selected from the following: polyacrylic acid (PAA) and its alkali metal salts, and modified polyacrylic acid (mPAA) and its alkali metal salts, SBR and CMC.
[0180] The binder may suitably be present in an amount of 0.5 to 20 wt%, preferably 1 to 15 wt% and most preferably 2 to 10 wt%, based on the total dry weight of the electrode composition.
[0181] The binder may optionally be present in combination with one or more additives that modify the properties of the binder, such as crosslinking accelerators, coupling agents and / or adhesion promoters.
[0182] The electrode composition may optionally include one or more conductive additives. Preferred conductive additives are non-electroactive materials that are included to improve the conductivity between the electroactive components of the electrode composition and the conductivity between the electroactive components of the electrode composition and the current collector. The conductive additive may be suitably selected from carbon black, carbon fiber, carbon nanotube, graphene, acetylene black, ketjen black, metal fiber, metal powder and conductive metal oxide. Preferred conductive additives include carbon black and carbon nanotube.
[0183] The one or more conductive additives may suitably be present in a total amount of 0.5 to 20 wt%, preferably 1 to 15 wt% and most preferably 2 to 10 wt%, based on the total dry weight of the electrode composition.
[0184] In a third aspect, the present invention provides an electrode comprising a granular material as defined in the first aspect of the present invention in electrical contact with a current collector. The granular material used to prepare the electrode of the third aspect of the present invention may have any of the features described as preferred or optional with respect to the first aspect of the present invention, and may be a granular material according to any one of aspects 1-1 to 1-16.
[0185] As used herein, the term current collector refers to any conductive substrate capable of carrying current to the electroactive particles in the electrode composition and carrying current out of the electroactive particles in the electrode composition. Examples of materials that can be used as current collectors include copper, aluminum, stainless steel, nickel, titanium and sintered carbon. Copper is a preferred material. The current collector is generally in the form of a foil or mesh having a thickness of 3 to 500 μm. The granular material of the present invention can be applied to one or both surfaces of the current collector to a thickness preferably in the range of 10 μm to 1 mm, for example 20 to 500 μm, or 50 to 200 μm.
[0186] Preferably, the electrode comprises an electrode composition as defined in accordance with the second aspect of the invention in electrical contact with a current collector.The electrode composition may have any of the features described as preferred or optional in relation to the second aspect of the invention.
[0187] The electrode of the third aspect of the present invention can be suitably prepared in the following manner: the granular material of the present invention (optionally in the form of an electrode composition of the present invention) is combined with a solvent and optionally one or more viscosity modifying additives to form a slurry. The slurry is then cast onto the surface of the current collector, and the solvent is removed to form an electrode layer on the surface of the current collector. Additional steps may be performed as appropriate, such as heat treatment for curing any binder and / or calendering of the electrode layer. The thickness of the electrode layer is suitably in the range of 20 μm to 2 mm, preferably 20 μm to 1 mm, preferably 20 μm to 500 μm, preferably 20 μm to 200 μm, preferably 20 μm to 100 μm, preferably 20 μm to 50 μm.
[0188] Alternatively, the slurry can be formed into a self-supporting film or mat comprising the particulate material of the present invention, for example by casting the slurry onto a suitable casting template, removing the solvent and then removing the casting template. The resulting film or mat is in the form of a cohesive, self-supporting object, which can then be combined with a current collector by known methods.
[0189] The electrode of the third aspect of the invention can be used as an anode of a metal ion battery. Therefore, in a fourth aspect, the invention provides a rechargeable metal ion battery comprising: an anode comprising an electrode as described above; a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions; and an electrolyte between the anode and the cathode. The granular material used to prepare the battery of the fourth aspect of the invention may have any of the features described as preferred or optional with respect to the first aspect of the invention, and may be a granular material according to any one of aspects 1-1 to 1-16.
[0190] The metal ions are preferably lithium ions. More preferably, the rechargeable metal ion battery of the present invention is a lithium ion battery, and the cathode active material is capable of releasing and reabsorbing lithium ions.
[0191] The cathode active material is preferably a composite material based on metal oxides. Examples of suitable cathode active materials include LiCoO2, LiCo 0.99 Al 0.01 O2, LiNiO2, LiMnO2, LiCo 0.5 Ni 0.5 O2、LiCo 0.7 Ni 0.3 O2、LiCo 0.8 Ni 0.2 O2、LiCo 0.82 Ni 0.18 O2、LiCo 0.8 Ni 0.15 Al 0.05 O2、LiNi 0.4 Co 0.3 Mn 0.3 O2 and LiNi 0.33 Co 0.33 Mn 0.34 O2. The cathode current collector generally has a thickness of 3 to 500 μm. Examples of materials that can be used as the cathode current collector include aluminum, stainless steel, nickel, titanium, and sintered carbon.
[0192] Electrolyte is suitably a non-aqueous electrolyte containing a metal salt (e.g., a lithium salt), and may include, but is not limited to, a non-aqueous electrolyte, a solid electrolyte, and an inorganic solid electrolyte. Examples of usable non-aqueous electrolyte solutions include aprotic organic solvents, such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, sulfolane, methyl sulfolane, and 1,3-dimethyl-2-imidazolidinone.
[0193] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ion dissociative groups.
[0194] Examples of inorganic solid electrolytes include nitrides, halides, and sulfides of lithium salts (such as Li5NI2, Li3N, LiI, LiSiO4, Li2SiS3, Li4SiO4, LiOH, and Li3PO4).
[0195] The lithium salt is suitably soluble in the selected solvent or solvent mixture. Examples of suitable lithium salts include LiCl, LiBr, LiI, LiClO4, LiBF4, LiBC4O8, LiPF6, LiCF3SO3, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li and CF3SO3Li.
[0196] In the case where the electrolyte is a non-aqueous organic solution, the metal ion battery preferably has a separator between the anode and the cathode. The separator is generally formed of an insulating material with high ion permeability and high mechanical strength. The separator generally has a pore size of 0.01 to 100 μm and a thickness of 5 to 300 μm. Examples of suitable electrode separators include microporous polyethylene films.
[0197] The separator may be replaced by a polymer electrolyte material, and in such a case, the polymer electrolyte material is present in both the composite anode layer and the composite cathode layer. The polymer electrolyte material may be a solid polymer electrolyte or a gel-type polymer electrolyte.
[0198] In a fifth aspect, the present invention provides the use of a particulate material as defined in the first aspect of the present invention as an anode active material. Preferably, the particulate material is in the form of an electrode composition as defined in the second aspect of the present invention, and most preferably, the electrode composition comprises one or more additional particulate electroactive materials as defined above. The particulate material used according to the fifth aspect of the present invention may have any of the features described as preferred or optional with respect to the first aspect of the present invention, and may be a particulate material according to any one of aspects 1-1 to 1-16. BRIEF DESCRIPTION OF THE DRAWINGS
[0199] Figure 1 The discharge capacity of the battery in the example is shown. DETAILED DESCRIPTION
[0200] Example
[0201] Example 1
[0202] Porous carbon framework particles (activated carbon particles) having the properties listed in Table 1 are provided.
[0203] Table 1
[0204]
[0205] *Volume fraction of micropores based on the total volume of micropores and mesopores
[0206] Silicon-carbon composite particles were prepared by depositing silicon within the pores of the porous carbon framework particles of Table 1 using monosilane gas at 475°C in a fixed bed reactor as described herein.
[0207] Example 2 - Compression Test
[0208] By using a high-precision micro compression tester (Shimadzu TM Model MCT-510), with a flat indenter of 50 μm diameter, a test force of 9.8 to 4903 mN and a test force of 7.75 mN·s- 1 The resistance of the granular material of the present invention to mechanical degradation was analyzed by compression testing of single particles under conditions of a loading rate of .
[0209] Particles of different sizes are selected from different composite particle samples (samples A1 to A4 are obtained by skeleton A, and samples B1 and C1 are obtained by skeleton B and C respectively). For each target particle size, at least 5 particles of size close to the target size are analyzed. Particle size is measured by the sample size measurement function of Model MCT-510, which uses the average value of the geometric mean diameter and length of the sample using the top image (obtained by optical microscope). Each particle is fastened between a flat indenter and a lower pressure plate, and then a test force of 9.8 to 4900mN is applied to the sample, and increases at the loading rate. The sudden increase in displacement indicates that fracture occurs in the particle. The force applied during the first fracture event is considered to be the particle crushing force. The crushing pressure is calculated by the crushing force applied divided by the area of the particle projected onto the indenter plane. The average crushing pressure of a plurality of different size samples of each composite material is considered to be the final crushing pressure. The results are shown in Table 2.
[0210] Table 2
[0211]
[0212]
[0213] It is understood that the crushing pressure of individual particles has a wide variation due to unpredictable differences between individual particles (e.g., the presence of defects, the shape of the particle when the particle contacts the indenter). To compensate for this inherent variability, the applicant also calculated the crushing pressure for P 1The average crush pressure obtained for a wide variety of different particles having a micropore fraction of 0.69 to 1.21, a micropore fraction of 0.54 to 0.78, and a silicon weight % of 45% to 59%. The summary results from multiple experiments with particle sizes of approximately 3 μm, 5 μm, 8 μm, 12 μm, and 15 μm are provided in Table 3 and clearly demonstrate the relationship between the particle size distribution and robustness of the composite particles. Tables 2 and 3 demonstrate that the particles of the present invention having a particle size of 8 μm or less (measured by a micro compression tester as described herein) have a crush pressure averaged over 5 particles of at least 250 MPa.
[0214] Table 3
[0215]
[0216] Example 3 - Electrochemical Testing
[0217] with a mixture comprising a 90 The negative electrode of silicon-carbon particles with particle size above and below 10 μm was used to prepare the test button cells. The dispersion of Carbon Super P (conductive carbon) in CMC binder was prepared in Thinky TM The silicon-carbon particle material is added to the conductive dispersion and mixed in a Thinky TM The mixture was mixed in a mixer for 30 min. SBR binder was then added to provide a CMC:SBR ratio of 1:1 to obtain a slurry with a weight ratio of granular silicon-carbon: CMC / SBR binder: conductive carbon of 70:16:14. The slurry was placed in a Thinky TM The mixture was mixed in a mixer for another 30 minutes, and then coated on a 10 μm thick copper substrate (current collector) and dried at 50° C. for 10 minutes, and then dried at 120-180° C. for 12 hours, thereby forming an electrode including an active layer on a copper substrate.
[0218] Full battery manufacturing
[0219] A full button cell was prepared using a circular negative electrode with a radius of 0.8 cm cut from this electrode with a porous polyethylene separator and a nickel manganese cobalt (NMC532) positive electrode. The positive and negative electrodes were designed to form a balanced pair so that the designed capacity ratio of the electrodes was about 0.9 (positive electrode: negative electrode). The electrolyte was then added to the cell before sealing, the electrolyte comprising 1M LiPF6 in a 7:3 solution of EMC / FEC (ethyl methyl carbonate / fluoroethylene carbonate) containing 3 wt% ethylene carbonate.
[0220] The full button cell was cycled as follows: a constant current was applied at a rate of C / 25 to lithiate the anode with a cutoff voltage of 4.3V. When cutoff was reached, a constant voltage of 4.3V was applied until a cutoff current of C / 100 was reached. The cell was then left to rest in the lithiated state for 10 minutes. The anode was then delithiated at a constant current of C / 25 with a cutoff voltage of 2.75V. The cell was then left to rest for 10 minutes. After this initial cycle, a constant current of C / 2 was applied to lithiate the anode with a cutoff voltage of 4.3V, followed by a constant voltage of 4.3V with a cutoff current of C / 40 and a rest time of 5 minutes. The anode was then delithiated at a constant current of C / 2 with a cutoff of 2.75V. This process was then repeated for the desired number of cycles. Figure 1 The discharge capacity in mAh / g (per gram of silicon-carbon composite particles) of the three test cells is plotted in .
[0221] All three silicon-carbon materials used in the negative electrode have similar silicon weight % and therefore similar initial discharge capacity. Each material also has an unoxidized silicon content of less than 10% at 800°C when analyzed by TGA as described herein. Samples X and Y have D 90 Particle size (D and 3.2 μm and 4.1 μm respectively) 50 The sample Z has a particle size of 6.5 μm and exhibits good capacity retention within the scope of the present invention. 50 Particle size and D outside the scope of the present invention 90 Without being bound by theory, these results are observed to be consistent with the hypothesis that the small size and high microporosity of the particles of the present invention are better able to accommodate stresses caused by silicon expansion during multiple cycles, as well as compressive stresses as demonstrated above.
Claims
1. A granular material comprising a plurality of composite particles, wherein the composite particles comprise: (a) a porous carbon framework comprising micropores and / or mesopores, Wherein, in the absence of any electroactive material or any other material occupying the pores of the porous carbon framework, the total pore volume of the micropores and mesopores is P 1 cm 3 / g, where P 1 represents a dimensionless number with a value of at least 0.6 and not more than 2.5, Among them PD 50 The pore size does not exceed 2 nm, where the PD 50 The pore size represents the volume median pore size based on the total volume of micropores and mesopores; The total pore volume of the micropores and mesopores and the PD 50 The pore size is determined according to ISO 15901-2 and ISO 15901-3 by nitrogen adsorption at 77K down to 10 -6 The relative pressure p / p0 is measured using density functional theory of quenched solids; and (b) an electroactive material located in the micropores and / or mesopores of the porous carbon framework; wherein the composite particle D 90 The particle size does not exceed 10 µm, wherein the electroactive material is silicon.
2. The granular material according to claim 1, wherein P 1 The value of is at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.15, or at least 1.
2.
3. A granular material according to claim 1 or claim 2, wherein P 1 The value of does not exceed 2.4, or does not exceed 2.2, or does not exceed 2, or does not exceed 1.8, or does not exceed 1.6, or does not exceed 1.5, or does not exceed 1.4, or does not exceed 1.3, or does not exceed 1.2, or does not exceed 1.1, or does not exceed 1.0, or does not exceed 0.
9.
4. The granular material according to claim 1, wherein the PD of the porous carbon skeleton is 50 The pore diameter is no more than 1.8 nm, or no more than 1.6 nm, or no more than 1.4 nm, or no more than 1.2 nm, or no more than 1 nm.
5. The granular material according to claim 1, wherein the PD of the porous carbon skeleton is 60 The pore diameter is no more than 3 nm, or no more than 2.5 nm, or no more than 2 nm, or no more than 1.8 nm, or no more than 1.6 nm, or no more than 1.4 nm, or no more than 1.2 nm.
6. The granular material according to claim 1, wherein the PD of the porous carbon framework 70 The pore diameter is no more than 3.5 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2.2 nm, or no more than 2 nm, or no more than 1.8 nm, or no more than 1.6 nm, or no more than 1.4 nm.
7. The particulate material according to claim 1, wherein the PD of the porous carbon framework 80 The pore diameter is not more than 5 nm, or not more than 4.5 nm, or not more than 4 nm, or not more than 3.5 nm, or not more than 3 nm, or not more than 2.5 nm, or not more than 2.2 nm, or not more than 2 nm, or not more than 1.8 nm, or not more than 1.6 nm.
8. The particulate material according to claim 1, wherein the PD of the porous carbon skeleton is 90 The pore diameter is not more than 10 nm, or not more than 8 nm, or not more than 6 nm, or not more than 5 nm, or not more than 4 nm, or not more than 3 nm, or not more than 2.5 nm, or not more than 2 nm.
9. The granular material according to claim 1, wherein the PD of the porous carbon skeleton is 95 The pore diameter is no more than 15 nm, or no more than 12 nm, or no more than 10 nm.
10. The particulate material of claim 1, wherein the porous carbon framework has a unimodal pore size distribution, wherein the pore size distribution represents the distribution of pore sizes of the porous carbon framework relative to the cumulative total internal pore volume.
11. The particulate material of claim 1, wherein the porous carbon framework has a bimodal or multimodal pore size distribution, wherein the pore size distribution represents the distribution of pore sizes of the porous carbon framework relative to the cumulative total internal pore volume.
12. The particulate material of claim 11, wherein the porous carbon framework has a bimodal or multimodal pore size distribution including at least one peak at less than 2 nm and at least one peak in the range of 2.5 to 20 nm.
13. The particulate material of claim 11, wherein the porous carbon framework has a bimodal or multimodal pore size distribution including at least one peak at less than 2 nm and at least one peak in the range of 2.5 to 15 nm.
14. The particulate material of claim 1, wherein the porous carbon framework comprises macropores with diameters ranging from greater than 50 nm to 100 nm, the total volume of the macropores as measured by mercury intrusion porosimetry being P 2 cm 3 / g, where P 2 No more than 0.2×P 1 , or not more than 0.1×P 1 , or not more than 0.05×P 1 , or not more than 0.02×P 1 , or not more than 0.01×P 1 , or not more than 0.005×P 1 .
15. The particulate material of claim 1, wherein at least a portion of the micropores and / or mesopores comprise void space that is completely encapsulated by the electroactive material.
16. The granular material of claim 1, wherein the D of the composite particles 90 Particle size not exceeding 9.5 µm, or not exceeding 9 µm, or not exceeding 8.5 µm, or not exceeding 8 µm, or not exceeding 7.5 µm, or not exceeding 7 µm, or not exceeding 6.5 µm, or not exceeding 6 µm, or not exceeding 5.5 µm, or not exceeding 5 µm, or not exceeding 4.5 µm, or not exceeding 4 µm.
17. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 0.5 to 7 µm.
18. The granular material of claim 17, wherein the D of the composite particles 50 The particle size is at least 1 µm, or at least 1.5 µm, or at least 2 µm, or at least 2.5 µm, or at least 3 µm.
19. A particulate material according to claim 17 or claim 18, wherein the D of the composite particles is 50 Particle size not exceeding 6.5 µm, or not exceeding 6 µm, or not exceeding 5.5 µm, or not exceeding 5 µm, or not exceeding 4.5 µm, or not exceeding 4 µm, or not exceeding 3.5 µm.
20. The granular material of claim 1, wherein the D of the composite particles 10 The particle size is at least 0.2 µm, or at least 0.5 µm, or at least 0.8 µm, or at least 1 µm, or at least 1.5 µm, or at least 2 µm.
21. The granular material of claim 1, wherein the D of the composite particles 99 Particle size not exceeding 25 µm, or not exceeding 20 µm, or not exceeding 18 µm, or not exceeding 15 µm, or not exceeding 12 µm, or not exceeding 10 µm, or not exceeding 9 µm, or not exceeding 8 µm, or not exceeding 7 µm, or not exceeding 6 µm, or not exceeding 5 µm.
22. The particulate material of claim 1, wherein the volume-based particle size distribution has a positively skewed distribution.
23. The granular material according to claim 1, wherein the composite particles are spherical particles, the average sphericity of the spherical particles is av is at least 0.
70.
24. The particulate material of claim 1, wherein the packing factor of the electroactive material in the porous carbon framework is no more than 55%, wherein the packing factor represents the proportion of the internal pore volume of the porous carbon framework occupied by the electroactive material.
25. The particulate material of claim 1, wherein the electroactive material has a filling factor in the porous carbon framework of 25% to 45%, wherein the filling factor represents the proportion of the internal pore volume of the porous carbon framework occupied by the electroactive material.
26. The granular material of claim 1, wherein the weight ratio of silicon to carbon is in the range of [0.5×P 1 To 1.7×P 1 ]:
1.
27. The granular material of claim 26, wherein the weight ratio of silicon to carbon is in the range of [0.5×P 1 To 1.3×P 1 ]:1, or in the range of [0.55×P 1 To 1.1×P 1 ]:1, or in the range of [0.6×P 1 To 1.1×P 1 ]:1, or in the range of [0.6×P 1 To 1×P 1 ]:1, or in the range of [0.6×P 1 To 0.95×P 1 ]:1, or in the range of [0.6×P 1 To 0.9×P 1 ]:1, or in the range of [0.65×P 1 To 0.9×P 1 ]:1, or in the range of [0.65×P 1 To 0.85×P 1 ]:1, or in the range of [0.65×P 1 To 0.8×P 1 ]:1, or in the range of [0.7×P 1 To 0.8×P 1 ]:
1.
28. The granular material of claim 26, wherein the weight ratio of silicon to carbon is in the range of [1×P 1 To 1.7×P 1 ]:1, or in the range of [1.1×P 1 To 1.7×P 1 ]:1, or in the range of [1.1×P 1 To 1.65×P 1 ]:1, or in the range of [1.1×P 1 To 1.6×P 1 ]:1, or in the range of [1.15×P 1 To 1.6×P 1 ]:1, or in the range of [1.15×P 1 To 1.55×P 1 ]:1, or in the range of [1.15×P 1 To 1.5×P 1 ]:1, or in the range of [1.2×P 1 To 1.5×P 1 ]:1, or in the range of [1.25×P 1 To 1.5×P 1 ]:1, or in the range of [1.3×P 1 To 1.5×P 1 ]:
1.
29. The particulate material of claim 1, wherein at least 90 weight percent of the mass of silicon in the composite particles is located within the internal pore volume of the porous carbon framework.
30. The particulate material of claim 1, wherein no more than 10% of the silicon content in the particulate material is unoxidized at 800°C when the particulate material is analyzed by TGA in air at a heating rate of 10°C / min.
31. The particulate material of claim 1, wherein the volume of micropores and mesopores of the composite particles measured by nitrogen adsorption is no more than 0.15 x P 1 , or not more than 0.10×P 1 , or not more than 0.05×P 1 , or not more than 0.02×P 1 .
32. The particulate material of claim 1, wherein the composite particles have a BET surface area of no more than 150 m 2 / g, or not more than 100 m 2 / g, or not more than 80 m 2 / g, or not more than 60 m 2 / g, or not more than 40 m 2 / g, or not more than 30 m 2 / g, or not more than 25 m 2 / g, or not more than 20 m 2 / g, or not more than 15 m 2 / g.
33. The particulate material of claim 1, wherein the composite particles have a BET surface area of at least 0.1 m 2 / g, or at least 1 m 2 / g, or at least 2 m 2 / g, or at least 5 m 2 / g.
34. The particulate material of claim 1, having a specific lithiation capacity of 1200 to 2340 mAh / g.
35. A composition comprising a particulate material as defined in any one of claims 1 to 34 and at least one other component.
36. A composition according to claim 35, comprising at least 50 wt%, or at least 55 wt%, or at least 60 wt%, or at least 65 wt%, or at least 70 wt%, or at least 75 wt%, or at least 80 wt%, or at least 85 wt%, or at least 90 wt%, or at least 95 wt% of the particulate material defined in any one of claims 1 to 34, based on the total dry weight of the composition.
37. A composition according to claim 35, comprising a particulate material as defined in any one of claims 1 to 34 and at least one further component selected from: (i) a binder; (ii) a conductive additive; and (iii) a further particulate electroactive material.
38. A composition according to claim 37 comprising at least one additional particulate electroactive material.
39. The composition of claim 38, wherein the at least one additional particulate electroactive material is selected from graphite, hard carbon, tin, germanium, gallium, aluminum and lead.
40. The composition of claim 37, comprising a binder in an amount of 0.5 to 20 wt%, or 1 to 15 wt%, or 2 to 10 wt%, based on the total dry weight of the composition.
41. The composition of claim 37, comprising one or more conductive additives in a total amount of 0.5 to 20 wt%, or 1 to 15 wt%, or 2 to 10 wt%, based on the total dry weight of the composition.
42. An electrode comprising a particulate material as defined in any one of claims 1 to 34 in electrical contact with a current collector.
43. An electrode according to claim 42, wherein the particulate material is in the form of a composition as defined in any one of claims 35 to 41.
44. A rechargeable metal ion battery, comprising: (i) an anode, wherein the anode comprises an electrode as claimed in claim 42 or claim 43; (ii) a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions; and (iii) an electrolyte between the anode and the cathode.
45. Use of a particulate material as defined in any one of claims 1 to 34 as an anode active material.
46. Use according to claim 45, wherein the particulate material is in the form of a composition as defined in any one of claims 35 to 41.
Citation Information
Patent Citations
Lithium secondary battery
JP2003100284A
A method of fabricating fibres composed of silicon or a silicon-based material and their use in lithium rechargeable batteries
WO2007083155A1
Anodic carbon material for lithium secondary battery, lithium secondary battery anode, lithium secondary battery, and method for manufacturing anodic carbon material for lithium secondary battery
US20110200874A1
Composite carbon materials comprising lithium alloying electrochemical modifiers
US20140272592A1
Sulfur-Carbon Composite Material, Its Application in Lithium-Sulfur Battery and Method for Preparing said Composite Material
US20150303458A1